Effect of Glucocorticoids Receptor Ligands on Renal Functions of mice induced by Nephrotoxic Poison Concanavalin-A - Haider Ali, Aqsa Mobeen, Afia Jari, Zain Imtiaz, Amtul Hafeez, Yasir Sadiq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: According to international society of nephrology about 2 million people die with AKI every year. Aim: To evaluate the effect of GR ligands on renal functions of mice induced by nephrotoxic poison Concanavalin-A. Study design: Experimental study. Methodology: The study was conducted at Agriculture University of Faisalabad-Pakistan following approval from ethical committee. Mice having age around 10 weeks, weighing 25 to 30 grams, kept under observation at animal house facility at University of Agriculture for 9 days. Subject animals (n=12) were equally divided into 3 groups, 1st was control group, 2nd was treated group and 3rd was untreated group. Renal markers, creatinine, urea and BUN were estimated from blood sample by using serum analyzer. The collected data was analyzed by using SPSS version 20. ANOVA ware applied with P-value< 0.05 as significant. Results: Analysis of kidney function test showed significance increase in creatinine, urea and BUN level in Con-A induced toxic group. They were normalized in pretreated groups receiving GR ligand (Dexa). Conclusion: It was concluded that glucocorticoids ameliorated the Con-A induced nephrotoxicity by significantly reducing the elevated kidney biomarker levels including creatinine, urea and BUN in mice serum. Keywords: Glucocorticoids, Serum Urea, BUN and Concanavalin-A.